Geothermal Energy Development in Türkiye: A Review - Abbas, Mohammed Faris; Mohammed, Ansam Adil; Mohammed, Akeel Abdullah; Channapattana, Shylesha; Parlak, Zekeriya (Al-Nahrain Journal for Engineering Sciences, 2024)
Türkiye possesses abundant geothermal resources. It is ranked seventh globally for this particular energy resources and grade among the first 5 in utilizing geothermal and thermal springs for various purposes such as electricity generation, residential cooling and heating, greenhouse operations, desiccating processes, thermal recreation, therapeutic applications, mining, agricultural uses, and aquaculture. The government's endorsement from renewable power sources is fueling growing interest on this particular energy sector. This article provides a comprehensive analysis of geothermal energy in select locations of Türkiye, including an assessment of its potential and various applications. The study seeks to provide a valuable involvement to the future advancements of a geothermal technology on Türkiye.